ANDROLOGICAL EVALUATION OF BULLS PRESENT ON RURAL PROPERTIES IN THE LOCAL DAIRY PRODUCTION ARRANGEMENT (APL) OF WEST GOIANO - Cristine Costa Pinto, Sâmara; Ribeiro Cordeiro, Fábio; Carla Cavalcante , Ana; Aurelio de Souza Ramos, Marco; José Gonçalves dos Santos, Klayto (Journal of Interdisciplinary Debates, 2023)
The andrological examination is a periodic evaluation that corresponds to the set of methods that aim to obtain information, such as changes in the reproductive system, pathologies and semen evaluation, with the aim of estimating the reproductive potential of males. The main objective of the examination is to select sires and estimate the reproductive potential of bulls, in addition, to identify animals with fertility problems. Therefore, the andrological examination must be seen as an integral part of the reproductive season, being a foundation to guarantee good results for beef and dairy cattle herds. Despite the increase in technology on properties in Brazil, the vast majority of producers have little information about the importance of carrying out andrological examinations before the reproductive season. Thus, the literature review aims to address the andrological examination and its benefits and encouragement in carrying out the examination on properties belonging to the local dairy production arrangement (APL) in western Goiás.